Proteomic analysis of nipple aspirate fluid to detect biologic markers of breast cancer - Sauter, E R (Nature Publishing Group, 2002)
The early detection of breast cancer is the best means to minimise disease-related mortality. Current screening techniques have limited sensitivity and specificity. Breast nipple aspirate fluid can be obtained noninvasively and contains proteins secreted from ductal and lobular epithelia. Nipple aspirate fluid proteins are breast specific and generally more concentrated than corresponding blood levels. Proteomic analysis of 1 μl of diluted nipple aspirate fluid over a 5–40 kDa range from 20 subjects with breast cancer and 13 with nondiseased breasts identified five differentially expressed proteins. The most sensitive and specific proteins were 6500 and 15 940 Da, found in 75–84% of samples from women with cancer but in only 0–9% of samples from normal women. These findings suggest that (1) differential expression of nipple aspirate fluid proteins exists between women with normal and diseased breasts, and (2) analysis of these proteins may predict the presence of breast cancer. British Journal of Cancer (2002) 86, 1440–1443. DOI: 10.1038/sj/bjc/6600285 www.bjcancer.com © 2002 Cancer Research UK